Generation of Evidence and Translation Into Practice: Lessons Learned and Future Directions. (14th November 2015) - McCabe, Aileen Mairéad; Kuppermann, Nathan
Abstract: The generation, validation, and then translation of definitive evidence to bedside evidence‐based practice is inconsistent and presents many challenges to emergency department (ED) researchers and clinicians. This is particularly true for diagnostic imaging in the ED, where benefits and drawbacks may be difficult to assess in the chaotic ED setting. This article describes, in large part, the experience of the Pediatric Emergency Care Applied Research Network (PECARN) in deriving and validating the traumatic brain injury prediction rules and how PECARN is translating these prediction rules into clinical practice. Furthermore, we discuss the potential for patient/parent shared decision‐making with a focus on patient‐centered outcomes in ED research and the role this shared decision‐making may play in enhancing knowledge translation and implementation of evidence‐based care in the ED.